Parental Behavior on Infants About ARTI Disease at Nggaha Ori Angu Public Health Center East Sumba Regency - ADOLFINA GARAMESA; JOHANA BABANG ATAMEHA; YOSEPHINA ELIZABETH SUMARTINI GUNAWAN (JURNAL KESEHATAN PRIMER, 2017)
Introduction: Acute Respiratory Tract Infection (ARTI) diseases are very common from mild to severe clinical manifestation. ARTI is on of main cause of death of the newborn and toddler. About 4 million people die because of ARTI each year, 98% caused by lower respiratory tract infection. The goal of this study is to know parent’s behavior of toddler on ARTI. Method: this study took 40 sample of parents who brought their children to Nggaha Ori Angu Primary Health Care (PHC) to have medical treatment from May to June 2017. This study is a descriptive study. The sample was taken with non-probability sampling technique, and consecutive sampling method, and questioner as study instrument. Results: the result of study of 40 sample on parent’s behavior on ARTI at Nggaha Ori Angu PHC are enough knowledge 23 people (57,5%), bad knowledge 17 people (42,5%), enough attitude 22 people (55%), bad attitude 18 people (45%), and those who have enough act 28 people (70%), bad act 12 people (30%). Summary: 3 behavior domains (knowledge, attitude, and act) of parents on ARTI diseases are at enough in a row as follow: enough knowledge 57,5%, enough attitude 55%, enough act 70% and none of them showed good knowledge, attitude and act on ARTI diseases.